The Effects of The Pharmaceutical Discovery Process on The Researcher Research must be a doctoral thesis - حنون نسرين غانم; حسن حيدر فليح (Journal of Legal Sciences, 2021)
The process of discovering pharmaceuticals is of great importance in our contemporary life, in a way that without life becomes almost impossible, as this process is the first building block in the field of pharmaceutical industries to search for new methods and means of treatment and treatment. But in fact, the fact that talking about this process is not that simple and easy, because this process is complicated and difficult in a way that makes it take a time range that in some cases reaches what is permissible ten years to reach a chemical formula that can be used later in the manufacturing process Pharmacokinetics, and during this long period of time, this process will have a set of effects, some of which are specific to the researcher discovered based on experience, and some of them are specific to the volunteer subject to them.